2018
DOI: 10.1002/jcb.26554
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cellular and serum proteome from tongue squamous cell carcinoma patient lacking addictive proclivities for tobacco, betel nut, and alcohol: Case study

Abstract: The intriguing molecular pathways involved in oral carcinogenesis are still ambiguous. The oral squamous cell carcinoma (OSCC) ranks as the most common type constituting more than 90% of the globally diagnosed oral cancers cases. The elevation in the OSCC incidence rate during past 10 years has an alarming impression on human healthcare. The major challenges associated with OSCC include delayed diagnosis, high metastatic rates, and low 5-year survival rates. The present work foundations on reverse genetic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 244 publications
(573 reference statements)
0
15
0
Order By: Relevance
“…Importantly, the lack of response in these subjects includes evidence for increases in miRNAs together with the downregulation of their corresponding gene targets. Among these miRNA gene targets were genes associated with cancer [e.g., IFI44L (36), RGL1 (37), MARCH1 (42), and MRPL17 (39)] and antiviral activity [e.g., IFIT5 (57) and TLR7 (1)]. Taken together with the upregulation of miRNAs (e.g., miR-155, let-7e, miR-370, miR-192, and miR-1275) that target IFN-inducible antiviral effector molecules (43), it is interpreted that these subjects may exemplify a response profile to Peg-IFN-a2a that would predict a return of plasma viral load, as was observed upon ART interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the lack of response in these subjects includes evidence for increases in miRNAs together with the downregulation of their corresponding gene targets. Among these miRNA gene targets were genes associated with cancer [e.g., IFI44L (36), RGL1 (37), MARCH1 (42), and MRPL17 (39)] and antiviral activity [e.g., IFIT5 (57) and TLR7 (1)]. Taken together with the upregulation of miRNAs (e.g., miR-155, let-7e, miR-370, miR-192, and miR-1275) that target IFN-inducible antiviral effector molecules (43), it is interpreted that these subjects may exemplify a response profile to Peg-IFN-a2a that would predict a return of plasma viral load, as was observed upon ART interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Whether in the TCGA-LUAD cohort or the three GEO cohorts for external verification, the seven-gene signature exhibited excellent performance for LUAD prognosis. Although previous studies have shown that the signature genes were related to a variety of cancers (liver cancer, breast cancer, oral cancer, and others), there have been few studies on the mechanism through which they participate in cancer progression (Li et al, 2017;Khowal et al, 2018;Uddin et al, 2018;Yao et al, 2019). Migration, proliferation, energy metabolism, and autophagy are all considered regulatory targets, but the underlying mechanism remains to be further elucidated (Hosgood et al, 2008;Wei et al, 2015;Jaiswal et al, 2018;Ma et al, 2020;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HPV16 DNA enhancers may cause activation of proto‐oncogenes, thereby, HPV16 integration may interfere with signaling networks functional in maintaining normal physiology of oral mucosa . Further studies are needed to elucidate the role of integration of HPV16 genome in OSCC with signaling networks, and the involvement of HPV genome variants in viral carcinogenesis in the oral cavity …”
Section: Discussionmentioning
confidence: 99%